Analisis Pengaruh Brand Image, Brand Trust Dan Psychology Terhadap Purchase Decision Laptop Di Lingkungan Mahasiswa(Studi Kasus : Universitas Kristen Krida Wacana, Univeristas Tarumanegara, dan Universitas Trisakti Jakarta Barat) - Jessi Fansisca; Saparso . (Ilmiah Manajemen Bisnis, 2014)
ABSTRACTThe purpose of this study was to analyze the influence of brand image, brand trust, and psychology towards on purchase decision of laptop in students environmental of Krida Wacana Christian University, Tarumanegara University, and Trisakti University West Jakarta. Samples in this study amounted to 210 people collected from student respondenets of Krida Wacana Christian University, Tarumanegara University, and Trisakti University. Based on a statistic test using SPSS software for windows version 19, showed that brand image, brand trust, and psychology simultaneously (F test) have a significant influence towards on purchase decision. Based on t test, the results of study showed that brand image has a positive influence and significant towards on purchase decision, brand trust has a negative influence and significant towards on purchase decision, and psychology has no influence towards on purchase decision.Keywords: Brand Image, Brand Trust, Psychology, Purchase Decision